PENGEMBANGAN BAHAN AJAR PENDIDIKAN AGAMA ISLAM MELALUI MULTIMEDIA PADA MATERI SYAJA’AH KELAS XI DI SMA NEGERI 4 BANDUNG - hermana, jajang eris (Atthulab: Islamic Religion Teaching and Learning Journal, 2019)
ABSTRACT Teaching materials are all forms of materials used to assist teachers / instructors in carrying out teaching and learning activities. The material in question can be either written materials or unwritten materials. With teaching materials allows students to learn a competence or basic competence in a coherent and systematic so that the accumulative able to master all the competencies as a whole and integrated. In the digital era like today, the teaching materials in learning Islamic Religious Education need to be developed, so the students are not behind the times. Development of teaching materials is called multimedia teaching materials. With this multimedia is expected to find new findings to learn. This multimedia teaching materials in preparing it required adequate knowledge and support skills, especially in operating equipment such as computers, cameras, video, and photo cameras. Technique of preparation of instructional materials include SK-KD-Indicator analysis, analysis of learning resources, selection and determination of teaching materials, and developing teaching materials. A teaching material at least does not include instructional instructions (student manual / teacher), competence to be achieved, content or content of learning materials, supporting information, and exercises. Keywords: Development, Islamic Education, Multimedia